Comportamento reprodutivo e produtivo de um sistema deprodução de leite ovino no México - Estrada-López, Carlos; Salvador-Flores, Omar; López-Díaz, Carlos Antonio; Maldonado-Jáquez, Jorge A. (Spei Domus, 2025)
The aim of this study was to characterize and evaluate the reproductive and productive performance of a sheep milk production unit that transforms the product into mature cheeses. The flock is composed of 484 crossbred East Friesian, Awassi, and Lacaune breed ewes, with an average weight of 70 kg, raised under a seasonal grazing feeding system with supplemental feeding in pens and controlled reproduction. Management was evaluated for one year, and information on reproductive and productive performance was collected, in terms of milk and cheese production. An average fertility rate of 77.8% was found; the months with the lowest fertility rates were February, March, April, and May. The annual production volume was 43,667 liters and was influenced by the herd size and the productive potential of each female. The average daily production was 547 ml-1 and 113 l-1 per ewe per year with 180 days in milk. The highest milk production was found from January to May. Cheese yield was 5.4 liters per kg of cheese and 21 kg of cheese per sheep present. The results provide relevant information for understanding the reproductive and productive performance of the sheep milk and cheese production system in Mexico, which is critical because most of these parameters are unknown.
Keywords: sheep; milk; reproductive seasonality; production; cheese yield